STRES PADA MANTAN PENGGUNA NARKOBA YANG MENJALANI REHABILITASI - Nawangsih, S.K.; Sari, Putri Rismala (Faculty of Psychology, Diponegoro University, 2016)
This is a qualitative phenomenological research aimed to understand stress of a former drug users whose under rehabilitation process. This research focused on factors that influencing and implications due to stresses of former drug users. Data collection method used is the method that used in this research is semi-structured interview, observations by non-participants, checklists, and documentations. Subject in this research determined by the cooperative ability of former drug users whose undergoing rehabilitation, which is three women as participants, at former drug users social rehabilitation office â€œMandiriâ€, Semarang. Through descriptive analysis of data research, factors that making former drug users stressed during rehabilitation process are loss of freedom, the guilty feelings, social affect such as ex-drug users label and other affect which cause worsen the conditions of a former drug users and the stressed level become higher. Furthermore, stress that experienced by the former users will affect their subjective conditions, cognitive behavior, and physiological conditions.